USES OF LIME -RICE HUSK ASH AND PLASTIC FIBERS AS MIXTURES-MATERIAL IN HIGH-PLASTICITY CLAYEY SUBGRADE: A PRELIMINARY STUDY - Agus Setyo Muntohar, Ario Muhammad (Jurnal Semesta Teknika UMY, 2007)
Silica produced from rice husk ashes have investigated successfully as a pozzolanic material in soil stabilization. However, rice husk ash cannot be used solely since the materials lack in calcium element. As a result, rice husk ash shall be mixed with other cementitious materials such as lime and cement to have a solid chemical reaction in stabilization process. The main objective of this study focused on bearing capacity of the stabilized clayey subgrade with lime-rice husk ash and fibers. The main laboratory test shall be compaction and CBR tests. The investigation results revealed that the inclusion of lime-rice husk ash-fiber into the soil decreased MDD and OMC. On the other hand, stabilization and reinforcement with lime-rice husk ash and fibers waste improved significantly the CBR values.